2023
DOI: 10.3390/gels9040280
|View full text |Cite
|
Sign up to set email alerts
|

Autoclaving-Triggered Hydrogelation of Chitosan-Gluconic acid Conjugate Aqueous Solution for Wound Healing

Abstract: Moist wound healing is known to heal wounds faster than dry wound healing. Hydrogel wound dressings are suitable for moist wound healing because of their hyperhydrous structure. Chitosan, a natural polymer, promotes wound healing by stimulating inflammatory cells and releasing bioactive compounds. Therefore, chitosan hydrogel has great potential as a wound dressing. In our previous study, physically crosslinked chitosan hydrogels were successfully prepared solely by freeze-thawing of chitosan-gluconic acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Absorption of this necrotic tissue debris passively clears the wound site and helps to recruit the other cells, such as macrophages and fibroblasts, for faster wound healing ( 44 ). Nevertheless, the moisture retention ability of the nanofibrous mats is also helpful for maintaining moisturization in the wound site for better cell survival ( 45 ). The porous networks of the nanofibrous membrane augment the extracellular matrix of the natural body tissue, which substantially helps for better cell adhesion and consecutive collagen synthesis needed for tissue healing ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of this necrotic tissue debris passively clears the wound site and helps to recruit the other cells, such as macrophages and fibroblasts, for faster wound healing ( 44 ). Nevertheless, the moisture retention ability of the nanofibrous mats is also helpful for maintaining moisturization in the wound site for better cell survival ( 45 ). The porous networks of the nanofibrous membrane augment the extracellular matrix of the natural body tissue, which substantially helps for better cell adhesion and consecutive collagen synthesis needed for tissue healing ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated the possibility of preparing hydrogels with chitosan derivatives as well as pure chitosan as a structure by the urea method. Herein, chitosangluconic acid conjugate (CG, chitosan chemically modified with gluconic acid on the amino groups) was used as a chitosan derivative [20][21][22]. The CG hydrogels were also successfully prepared using the urea method (Figure 1k).…”
Section: Preparation Of Chitosan Hydrogelsmentioning
confidence: 99%
“…We previously reported that chitosan-gluconic-acid conjugate (CG) was soluble in a pH-neutral aqueous solution [20,21], and the solution formed a physically crosslinked hydrogel by autoclaving [22], which is steam sterilization at high temperatures and high pressure (121 • C, 2 atm), without toxic additives. The CG hydrogel has good biological properties derived from chitosan for wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is promising for the preparation of novel hydrogels, which are widely used in fields of medicine [4], drug delivery [5], and tissue engineering [6], especially the superiority in the field of wound healing [7,8]. Chitosan-gluconic acid conjugate hydrogels [9] under autoclaving (121 • C, 20 min) simultaneously achieved gelation of the solution and sterilization of the hydrogel, which retained favorable biological properties and was promising as wound dressings. Chitosan hydrogels can be linked to biosensor physical elements for disease diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%